Ageing promotes early T follicular helper cell differentiation by modulating expression of RBPJ. Issue 1 (2nd January 2021) - Webb, Louise M. C.; Fra‐Bido, Sigrid; Innocentin, Silvia; Matheson, Louise S.; Attaf, Noudjoud; Bignon, Alexandre; Novarino, Julien; Fazilleau, Nicolas; Linterman, Michelle A.
Abstract: Ageing profoundly changes our immune system and is thought to be a driving factor in the morbidity and mortality associated with infectious disease in older people. We have previously shown that the impaired immunity to vaccination that occurs in aged individuals is partly attributed to the effect of age on T follicular helper (Tfh) cell formation. In this study, we examined how age intrinsically affects Tfh cell formation in both mice and humans. We show increased formation of Tfh precursors (pre‐Tfh) but no associated increase in germinal centre (GC)‐Tfh cells in aged mice, suggesting age‐driven promotion of only early Tfh cell differentiation. Mechanistically, we show that ageing alters TCR signalling which drives expression of the Notch‐associated transcription factor, RBPJ. Genetic or chemical modulation of RBPJ or Notch rescues this age‐associated early Tfh cell differentiation, and increased intrinsic Notch activity recapitulates this phenomenon in younger mice. Our data offer mechanistic insight into the age‐induced changes in T‐cell activation that affects the differentiation and ultimately the function of effector T cells. Abstract : Ageing alters TCR signalling which drives expression of the Notch‐associated transcription factor, RBPJ. This results in enhanced differentiation into T follicular helper cell precursors.